Upaya Anggota Jaringan Gusdurian Pasuruan dalam Membina Toleransi Antar Umat Beragama - Maria Ganis Prasasti; Maya Mustika Kartika Sari (CV. Ulil Albab Corp, 2023)
This study aims to determine the efforts of members of the Pasuruan gusdurian network in fostering tolerance between religious people. This research uses a qualitative approach with a descriptive research design. Data collection techniques through in-depth interviews, passive participation observation and documentation. The collected data was analyzed using a model from Miles and Huberman through four stages starting from data collection, data reduction, data presentation and drawing conclusions. This research uses Max Weber's theory of Social Action. The research location was adjusted to the location of the informants and the location of the gusdurian network activities in the Pasuruan area. The results showed that the underlying thing for members of the gusdurian network to foster tolerance is based on the experience of interfaith contact, inspiration for Gusdur's thoughts and good meaning of tolerance. Efforts made to foster tolerance through activities and programs are, Gus Dur study forum, tolerance day commemoration and commemoration of Gusdur's haul, encounters with different groups and religions, utilization of social media content and the Violence Prevention Initiative Program.